Graphene Based Aerogels: Fundamentals and Applications as Supercapacitors - Yasir Beeran Pottathara (5309153) (2020)
Super Capacitors have attained a huge amount of attention due to their outstanding features and characteristics such as high-power density, excellent charge/discharge routine, and tendency of a longer lifetime. Graphene, a single layer of hexagonally crammed carbon atoms, has always been considered as an outstanding material for super capacitor fabrication due to its higher theoretical surface area, high electrical conductivity, stable thermal properties, and its mechanical and chemical properties. Super capacitor electrode resources which are based on 3D network/aerogel structures are resultant of graphene is a prime area of research due to their porous structure and lattice which meets the expense of rapid electron transport, higher stability, and a good cycle performance. This review intents to summarize the fundamentals and the fabrication strategies of 3D graphene aerogels. Other Information Published in: Journal of Energy Storage License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.est.2020.101549